Elucidating The Effects of Antimycin A on Metabolome of Pancreatic Beta Cells Using Liquid Chromatography-Mass Spectrometry - Ngamratanapaiboon, Surachai; Yambangyang, Pracha; Akrachalanont, Pilaslak; Hongthawonsiri, Patipol; Pornchokchai, Krittaboon; Wongpitoonmanachai, Siriphattarinya; Pholkla, Petchlada; Srikornvit, Napatarin; Mo, Jiajun; Devakul Na Ayutthaya, Watcharaporn (Journal of Basic and Applied Pharmacology, 2023)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by impaired glucose homeostasis, insulin resistance, and beta cell dysfunction. Emerging evidence suggests that the mitochondrial electron transport chain (ETC) plays a pivotal role in regulating beta cell function and glucose homeostasis. Antimycin A is a known inhibitor of the mitochondrial ETC complex III, which could potentially impact beta cell metabolism and function. In this study, we aimed to investigate the effect of antimycin A on beta cell metabolism using a metabolomics-based LC-MS approach. Murine pancreatic beta cells (MIN 6) were treated with antimycin A (1 µM) for 2 hr. Control cells were treated with glucose. Metabolites were extracted from the cells, and LC-MS analysis was performed using a high-resolution mass spectrometer. Metabolic profiling was performed using the MetaboAnalyst 5.0. Metabolites were identified and quantified using a metabolite library. Statistical analysis was performed using multivariate and univariate approaches. Metabolic profiling of antimycin A -treated beta cells revealed significant alterations in cellular metabolism compared to control cells. The most significant changes were observed in the metabolism of amino acid, nucleotides, and the tricarboxylic acid (TCA) cycle. Antimycin A can affect these, possibly leading to insulin secretion impairment. The results of this study highlight the potential of antimycin A as a valuable tool for exploring the impact of mitochondrial function on beta cell metabolism and function. The observed changes in metabolite profiles in antimycin A-treated cells shed light on the metabolic pathways crucial for beta cell function and may offer valuable insights for the development of novel diabetes therapies. The metabolomics analysis conducted using LC-MS in this study represents a powerful approach for investigating the consequences of mitochondrial dysfunction on cellular metabolism.